Application of Polynomial Rocking Bearings as Seismic Isolation System on Irregular Bridges - Anugerahputra, Krisna Febrian; Tzu Ying, Lee; Wibowo, Ari (Civil and Environmental Science Journal (CIVENSE), 2018)
Friction Pendulum System (FPS) is one of the conventional sliding isolators which widely used and effectively proved to reduce seismic hazard in far-fault earthquakes. However, it may not be effective when the structures are induced by near-fault earthquakes because the earthquake’s period is usually close to the isolation period. In this study, a Polynomial Rocking Bearing (PRB) which has variable isolation stiffness is used to improve the performance of seismic isolation systems applied on irregular bridges under near-fault earthquakes. The PRB is composed by an articular joint and concave rocking surface. The rocking surface is defined by a sixth-order polynomial function. Based on previous studies, the PRB has been verified to effectively suppress the large isolator displacement subjected to near-fault earthquakes on building and regular bridges. However, it has not been used yet in the irregular bridges. This study aims to analyze the behaviour of Polynomial Rocking Bearing installed on an irregular bridge. As compared with Friction Pendulum Systems (FPS), the performance of PRBs is much better to effectively suppress the displacement of the bridge deck in both near and far-fault earthquakes.